The Role of Emotional Intelligence Domains on Working Remotely Norm During Post-Pandemic Era - Johar, Siti Sarawati; Razali, Nur Azah; Saleh, Nor Shela; Md Nor, Noranifitri; Razali, Nurul Aimi; Damin, Zahrul Akmal (2024)
This study investigates the relationship between emotional intelligence and working remotely. Additionally, this study looks at how emotions in each of the four categories of emotional intelligence domain play a role in influencing Malaysian civil servants' norm of working remotely. The study sample consists of respondents from both academic and non-academic service categories. To assess the first variable, researchers who underwent instrument, face , and construct validation created the questionnaire known as the Emotional Intelligence Domain Inventory (EIDInv; Siti Sarawati Johar, 2021). The questionnaire used to measure the second variable is called the Work from Home Norm Instrument. It was adopted from the Work from Home Challenge COVID-19 Instrument (WFHI-CvdC; Siti Sarawati Johar, 2021). To determine how the four domains of emotional intelligence impact the emotional well-being of a typical homeworker, this study used regression analysis. The study's conclusions show how each variable's relationships and effects have a significant influence. This study expands our understanding of emotional and behavioral well-being in general. It provides valuable information for future researchers examining the topic from the organizational psychology perspective and its connections to the social and economic domains of the community.